Inequality of Opportunity and Intergenerational Persistence in Latin America - Paolo Brunori; Francisco H. G. Ferreira; Guido Neidhöfer (Institute of Labor Economics (IZA), 2024)
How strong is the transmission of socio-economic status across generations in Latin America? To answer this question, we first review the empirical literature on intergenerational mobility and inequality of opportunity for the region, summarizing results for both income and educational outcomes. We find that, whereas the income mobility literature is hampered by a paucity of representative datasets containing linked information on parents and children, the inequality of opportunity approach – which relies on other inherited and pre-determined circumstance variables – has suffered from arbitrariness in model selection. Two new data-driven approaches – one aligned with the ex-ante and the other with the ex-post conception of inequality of opportunity – are introduced to address this shortcoming. They yield a set of new inequality of opportunity estimates for twenty-seven surveys covering nine Latin American countries over various years between 2000 and 2015. In most cases, more than half of the current generation's inequality is inherited from the past – with a range between 44% and 63%. We argue that on balance, given the parsimony of the population partitions, these are still likely to be underestimates.
Keywords: D31; I39; J62; O15; 330; inequality of opportunity; intergenerational mobility; Latin America